2013
DOI: 10.3892/or.2013.2821
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-C and VEGF-D overexpression is more common in left-sided and well-differentiated colon adenocarcinoma

Abstract: Tumour vessel network formation, including blood and lymph vessels, is a major step involved in the process of carcinogenesis. The discovery of vascular growth factors has led to a better understanding of tumour biology, thus, creating new possibilities for cancer treatment that targets angiogenesis within tumour-associated stroma, including therapy for colon cancer patients. The present study evaluated the relationships between increased expression of lymphangiogenic factors (VEGF-C and VEGF-D) and vessel den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…At the same time pT3-4 poorly differentiated and mucinous tumours were found significantly more frequently in the right side of the colon. Similar results were obtained in another study evaluating simultaneous expression of VEGF-C and VEGF-D in colon pT1-4 cancer cells [ 16 ]. Differences in clinical parameters, histological differentiation, and prognosis in cancers located in the left and right sides of the colon are discussed in many papers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the same time pT3-4 poorly differentiated and mucinous tumours were found significantly more frequently in the right side of the colon. Similar results were obtained in another study evaluating simultaneous expression of VEGF-C and VEGF-D in colon pT1-4 cancer cells [ 16 ]. Differences in clinical parameters, histological differentiation, and prognosis in cancers located in the left and right sides of the colon are discussed in many papers.…”
Section: Discussionsupporting
confidence: 89%
“…1 ), which show better prognosis for pT3-4 tumours with present VEGF-C expression (left-sided, moderately and well differentiated tumours). In a previously published paper, we analysed simultaneous expression of lymphangiogenic factors (VEGF-C and VEGF-D) in colon pT1-4 cancer cells [ 16 ]. Both VEGF-C and VEGF-D are involved in the formation of lymphatic microvessels, and through the capability of VEGFR-2 receptor binding they also mediate neovascularisation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is endothelial cell specific heparin-binding growth factor, which is critical for the proliferation and metastatic potential of colon carcinoma cells [ 13 , 14 ]. We further detected the VEGF protein expression and found that its expression was decreased in p-miR-21-ASO transfected group compared with p-Cont transfected group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of tumor vessel network, including blood and lymph vessels, is an important stage in carcinogenesis process. The discovery of vascular growth factors has resulted into a better understanding of tumor biology, so opening new possibilities in treatment of cancer to target angiogenesis within tumor-associated stroma, including therapy for colon cancer patients is of great importance (Szajewski et al, 2014).…”
Section: Clinical Significance Of Serum Vascular Endothelial Growth Fmentioning
confidence: 99%